Bulgaria : The Road to Successful EU integration, The Policy Agenda, A Country Economic Memorandum - World Bank (Washington, DC, 2012)
As Bulgaria approaches European Union accession, it has the opportunity to narrow the income gap, and raise productivity and investment, and set the economy on a higher growth path. To address these challenges and accelerate convergence with the European Union, this report proposes a reform agenda focused on five areas: productivity and growth, trade and investment integration, public expenditure policy, labor market adjustment, and the regulatory and institutional framework. Chapter 1 focuses on stability, growth dynamics, and integration. The analysis of these three fundamental dimensions over time is complemented with cross-country comparisons. Chapter 2 examines the foundations of Bulgaria's growth performance over the last several years in terms of the drivers of growth, intra-sectoral restructuring, growth accounting, and potential output growth. Trade policy, trade and FDI dynamics, and recent trends in trade performance are examined in Chapter 3, while Chapter 4 discusses the reforms needed in public expenditure policies to support deepening trade integration. Chapter 5 covers labor market performance and labor market policies and institutions. In Chapter 6, selected dimensions of the institutional framework for growth and competitiveness are examined, and Chapter 7 discusses macroeconomic policies aimed at addressing risks and vulnerabilities and supporting progress in monetary integration. Finally, Chapter 8 presents a summary of the main conclusions drawn from the report.